Investigation on energy storage and conversion properties of multifunctional PANI-MWCNT composite. (5th April 2018) - Roy, Atanu; Ray, Apurba; Saha, Samik; Das, Sachindranath
Abstract: Polyaniline-multiwalled carbon nanotube (PANI-MWCNT) composite synthesized through chemical polymerization is investigated as a possible electrode material for supercapacitor as well as an electro-catalyst for hydrogen evolution reaction (HER) in acidic medium. UV–Vis spectroscopy, FTIR spectroscopy and field emission scanning electron microscopy (FESEM) have been used to characterize the electrode material. The binder-free electrodes were prepared and they exhibit a specific capacitance of 540.29 F g −1 at a scan rate of 2 mV s −1 in 1 M H2 SO4 electrolyte. The material exhibits excellent pseudocapacitive behaviour due to the presence of PANI with long-term cyclic stability of 87.4% retention after 5000 cycles. PANI-MWCNT composite also shows good HER activity, with overpotential of −395 mV. Highlights: Supercapacitive and electro-catalytic performances of PANI-MWCNT have been studied. Optimum loading of MWCNT in PANI has been found for the best performance. Highest specific capacitance of 540.29 F g −1 was obtained with long term stability. Metal-free composite shows good HER activity, with overpotential of −395 mV.